Peran Program Kepemudaan KIPAN Lampung dalam Pemberantasan Narkoba pada Generasi Muda - Intan Rasita; Nayla Azizah; Mutiara Putri Syahrani; Teqi Prasetyo Sulaksono; Susilo Susilo (JURNAL ILMIAH NUSANTARA, 2025)
The Young Generation represents the future of the nation's struggle and human resources for national development. The young generation must be able to carry out roles and responsibilities that guarantee the sustainability of our nation and country, and act as agents of change. The study used a qualitative method with a descriptive approach as the main method in data collection, and the data in this method was collected through in-depth interview analysis with the general chairman of KIPAN Lampung as a resource person. The results of this study indicate that the involvement of the young generation in efforts to combat drugs shows their seriousness in facing this challenge, fighting to become a more positive group, and daring to voice the message "Say no to drugs.", excessive drug use causes significant changes in behavior and attitudes, resulting in reduced ability to reason, and emotional management, leading to deviant, and in overcoming these problems the government launched the anti-drug youth core cadre program (KIPAN), a leading initiative to prevent and eradicate drug trafficking in Indonesia, by involving the young generation as agents of change. This program provides training, education and services intended to prepare young leaders, who are committed to fighting drugs.